New species and records of the genus Dendrothrips Uzel (Thysanoptera, Thripidae) from Saudi Arabia - Rasool, Iftekhar; Ansi, Amin N. Al; Aldhafer, Hathal M. (Zootaxa, 2026)
Three species of Dendrothrips are recorded from Saudi Arabia, and a key provided to the species of Dendrothrips from the Arabian Peninsula. D. longipalpus sp. nov. has prominent pronotal posteroangular setae. D. cameroni Priesner and D. phyllireae Bagnall are recorded as new to the country. Diversity in the presence or absence of prominent pronotal posteroangular setae among Dendrothrips species is considered.